DEVELOPMENT AND IMPROVEMENT OF SWEETPOTATO PICKLES - Tan, Julie D.; Forio, Edna E. (Annals of Tropical Research, 1997)
The suitability of sweetpotato for pickling was investigated. The use of low salt (LS) and high salt (H) was tried in the curing process. LS was found to be an effective method for curing sweetpotato. This process was further improved by heat and chemical treatments and reduction of curing time from 11 wks to 6 days was realized. Blanching was found to contribute a profound improvement on the quality of sweetpotato. The starchiness of pickle was greatly reduced through heat treatment before curing. The reduction of curing time still favored the production of relatively higher amount of acid which is necessary for the souring process The sweet-type Jamaica Sweet-mixed and Spread Relish pickles, were found to be more acceptable than the sour-type Genuine Dill pickles.